Resveratrol Ameliorates Vancomycin-Induced Testicular Dysfunction in Male Rats - Fahad S. Alshehri (Medicina, 2023)
Background and Objectives: Numerous studies have indicated that antibiotics may adversely affect testicular and sperm function. As an alternative to penicillin, vancomycin is a glycopeptide antibiotic developed to treat resistant strains of Staphylococcus aureus. A few studies have suggested that vancomycin could cause testicular toxicity and apoptosis. Vancomycin, however, has not been investigated in terms of its mechanism of causing testicular toxicity. Materials and Methods: An experiment was conducted to investigate the effects of resveratrol (20 mg/kg, oral gavage) against vancomycin (200 mg/kg, i.p.) on the testicular function of Wistar rats for one week (7 days). There were three subgroups of animals. First, saline (i.p.) was administered to the control group. Then, in the second group, vancomycin was administered. Finally, vancomycin and resveratrol were administered in combination in the third group. Results: After seven days of vancomycin treatment, testosterone levels, sperm counts, and sperm motility were significantly reduced, but resveratrol attenuated the effects of vancomycin and restored the testosterone levels, sperm counts, and sperm motility to normal. In the presence of resveratrol, the vancomycin effects were attenuated, and the luteinizing hormone and follicular hormone levels were normalized after seven days of treatment with vancomycin. Histologically, vancomycin administration for seven days caused damage to testicular tissues and reduced the thickness of the basal lamina. However, the resveratrol administration with vancomycin prevented vancomycin’s toxic effects on testicular tissue. Conclusion: Resveratrol showed potential protective effects against vancomycin-induced testicular toxicity in Wistar rats.